The elusive banana weevil Cosmopolites sordidus Germar - Karamura, E.B.; Gold, C. (International Society for Horticultural Science, 2000)
The banana weevil Cosmopolites sordidus Germar, has evaded all efforts to manage it in all banana-based cropping systems except the commercial plantation banana system, where the 2 to 3 year crop cycle and the intensity of management limit the pest survival in that system. Conversely, in backyard and subsistence banana systems, predominant in Africa, the perennial cropping of banana and plantain, coupled with the planting of infested material, readily supports the pest survival strategies, resulting in pest build-up and crop losses. This hypothesis may explain why the banana weevil has eluded control in perennial banana cropping systems. This review article provides a summary of available literature on weevil pest management strategies with the intent of identifying loopholes in the conceptualization of the problem and possible research information gaps in the current management activities. The review attributes current weevil pest management problems to the poor understanding of the linkages between weevil biology and associated ecological strategies, as well as the broad banana and plantain systems and human activities. This review article urges that the solution to the weevil pest problems lies in the careful integration of biological applications and socioeconomic strategies in the context of the broad ecological farming systems.